Mind in the waters a book to celebrate the consciousness of whales and dolphins - McIntyre, Joan (New York Charles Scribner's Son, 1974)
Calls attention to the need to stop the senseless murder of whales and dolphins and promotes a human awareness of the sensitivity and creativity of these creatures.
"A collection that outlines the capabilities and consciousness of whales and dolphins. Drawing on mythology as well as the most advanced scientific findings, on poetry as well as natural history, on statistics as well as photographs, it is a basic compendium of information about whales and dolphins and a picture of the new understandings that seem to lie just beyond our present knowledge"--Dust cover.
Whales weep not : a poem / D. H. Lawrence -- Invitation / Joan Mc Intyre -- The trapped whale / Farley Mowat -- part 1. Myths and beginnings. Magic words : a poem / Eskimo ; The dolphin rider / Charles Doria ; The evolution of Cetacean intelligence / Sterling Bunnel -- part 2. Brains and consciousness. On awareness / Joan Mc Intyre ; A feeling of weirdness / John Lilly ; The whale brain : input and behavior / Myron Jacobs ; The whale brain : the anatomical basis of intelligence / Peter Morgane ; Mind play / Joan Mc Intyre ; The whale object : a portfolio of drawings / Larry Foster ; Iceberg / Joan Mc Intyre ; Going out to meet the moon whales : a poem / Paule Barton ; For a coming extinction : a poem / W. S. Merwin -- part 3. Living in the sea. The ways of whales / Peter Warshall ; Leviathan : a poem / Pablo Neruda ; Body state communication among Cetaceans / John Sutphen -- part 4. Discovery and response. Observations of a Cetacean community / Gregory Bateson ; For the death of 100 whales : a poem / Michael Mc Clure ; The whale show / Paul Spong ; Prayer of a man who found a dead killer whale : a poem / Kwakiutl ; Say "Rooo-beee!" / Malcom Brenner ; Love swim / William Curtsinger ; Mind in the waters / Joan Mc Intyre -- part 5. Let us act. Let us act / Joan Mc Intyre ; One strand in the rope of concern / Scott Mc Vay ; The case for a world moratorium on whaling / Victor Scheffer ; The great whales and the International Whaling Commission / Lee Talbot ; Re-creation / Joan Mc Intyre.
"This book was edited and prepared for publication by The Yolla Bolly Press in collaboration with Project Jonah. The work was done in Sausalito, California, between January and June of 1974"--Title page verso.
Includes bibliographical references and index.
Also issued online.
Keywords: Whales; Dolphins; Animal Intelligence